The application of split step fourier migration to interpreting GPR data in Vietnam - Trung, Dang Hoai; Giang, Nguyen Van; Van, Nguyen Thanh; Thuan, Nguyen Van; Triet, Vo Minh (Vietnam Journal of Marine Science and Technology, 2017)
Migration methods play an essential role in processing ground penetrating radar data. For estimating electromagnetic propagation velocity distribution, the finite - difference migration is used because of its reliable performance with high noise conditions. To optimize this migration algorithm, we propose using energy diagram as a criterion of looking for the correct velocity. If the velocity varies laterally and vertically, split step Fourier migration is used for creating a true image of subsurface structures. We applied these steps to real data in Vietnam. The results verified on field data show that migrated images with calculated velocity from energy diagram have the best quality.